Applications of carbon dots on tumour theranostics. Issue 2 (14th January 2021) - Wu, Hao; Su, Wen; Xu, Huimin; Zhang, Yang; Li, Yunchao; Li, Xiaohong; Fan, Louzhen
Abstract: Carbon dots (CDs) have been extensively investigated as prime candidates for developing tumour theranostic platform due to their tunable fluorescence emission and excitation, good photostability, high water solubility and biocompatibility. Herein, we will update the recent research and latest development on the preparation, hydrophilicity, biotoxicity and optical property of CDs, as well as their applications in multimodal bioimaging and anticancer drug delivery. We will mainly highlight their applications in in vivo imaging and tumour‐targeted theranostics with a special emphasis on large amino acid‐mimicking carbon quantum dots‐based tumour theranostics through a large neutral amino acid transporter 1 (LAT1)‐mediated targeted strategy. Finally, we will also discuss the current status, key challenges and future directions of CDs in tumour theranostics. We expect that this review will summarize recent advances to inspire more researches on CDs for biomedical and clinical applications in the near future. Abstract : The applications of CDs in tumour theranostics are mainly discussed, with a special emphasis on large amino acid‐mimicking carbon quantum dots‐based tumour theranostics through a LAT1‐mediated targeted strategy. Current status, challenges and future directions of CDs in tumour theranostics will also be discussed.